ORGANIZATIONAL ECONOMIC MECHANISM OF ENSURING PERSONAL SECURITY IN THE SYSTEM OF ECONOMIC SECURITY (World Bulletin of Management and Law, 2023)
The article discusses the current state of research on personal economic security, emphasizes the need to study subjective ideas about the level and components of personal economic security, existing threats and ways to protect against them. The work contains the results of studying the subjective ideas of young students about the most pressing threats to personal economic security, which shows that the student audience has certain skills in identifying threats to the economic security of their families, assessing their importance showsas well as the ability to formulate recommendations to eliminate identified threats. As a real threat to the economic security of a person, students often name threats such as loss of sources of income, a decrease in the level of income or their initial low level, ineffective personal financial planning, macroeconomic problems and disability due to health problems. Despite the fact that most of the mentioned threats are mainly external to the family person, the students' work is dominated by recommendations to reduce harm from these threats by the person himself, which may indicate a trend of decreasing risk